Controllability of Impulsive Non–Linear Delay Dynamic Systems on Time Scale - Akbar Zada; Luqman Alam; Poom Kumam; Wiyada Kumam; Gohar Ali; Jehad Alzabut (IEEE Access, 2020)
In this paper, we obtain the results of controllability for first order impulsive non–linear time varying delay dynamic systems and Hammerstein impulsive system on time scale, using the theory of fixed points such as Banach fixed point theorem combined with Lipchitz conditions and non linear functional analysis. We also provide examples to support our theoretical results.